Beyond prediction: Off‐target uses of artificial intelligence‐based predictive analytics in a learning health system - Jessica Keim‐Malpass; Liza P. Moorman; Oliver J. Monfredi; Matthew T. Clark; Jamieson M. Bourque (Wiley, 2023)
Abstract Introduction Artificial‐intelligence (AI)‐based predictive analytics provide new opportunities to leverage rich sources of continuous data to improve patient care through early warning of the risk of clinical deterioration and improved situational awareness.Part of the success of predictive analytic implementation relies on integration of the analytic within complex clinical workflows. Pharmaceutical interventions have off‐target uses where a drug indication has not been formally studied for a different indication but has potential for clinical benefit. An analog has not been described in the context of AI‐based predictive analytics, that is, when a predictive analytic has been trained on one outcome of interest but is used for additional applications in clinical practice. Methods In this manuscript we present three clinical vignettes describing off‐target use of AI‐based predictive analytics that evolved organically through real‐world practice. Results Off‐target uses included:real‐time feedback about treatment effectiveness, indication of readiness to discharge, and indication of the acuity of a hospital unit. Conclusion Such practice fits well with the learning health system goals to continuously integrate data and experience to provide.